2013
DOI: 10.7454/mst.v15i2.938
|View full text |Cite
|
Sign up to set email alerts
|

Cassava Pulp as a Biofuel Feedstock of an Enzymatic Hydrolysis Proces

Abstract: Cassava pulp, a low cost solid byproduct of cassava starch industry, has been proposed as a high potential ethanolic fermentation substrate due to its high residual starch level, low ash content and small particle size of the lignocellulosic fibers. As the economic feasibility depends on complete degradation of the polysaccharides to fermentable glucose, the comparative hydrolytic potential of cassava pulp by six commercial enzymes were studied. Raw cassava pulp (12% w/v, particle size <320 µm) hydrolyzed by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In terms of enzyme supplementation, the high yield of glucose indicates the potential use of enzymatic-hydrothermally treated cassava pulp has been reported by Djuma'ali et al (2011). Sriroth et al (2000) also have reported that enzymatic treatment of cassava pulp increases the susceptibility of starch molecules to alpha-amylase hydrolysis thereby increases the amount of reducing sugar for further fermentation by microorganisms.…”
Section: Discussionmentioning
confidence: 93%
“…In terms of enzyme supplementation, the high yield of glucose indicates the potential use of enzymatic-hydrothermally treated cassava pulp has been reported by Djuma'ali et al (2011). Sriroth et al (2000) also have reported that enzymatic treatment of cassava pulp increases the susceptibility of starch molecules to alpha-amylase hydrolysis thereby increases the amount of reducing sugar for further fermentation by microorganisms.…”
Section: Discussionmentioning
confidence: 93%
“…Typically, raw substrate hydrolysis requires the synergistic interaction of enzyme composites to achieve complete saccharification (conversion yield ≥80%), such as cooperation of α-amylase and glucoamylase in starch hydrolysis [73]. In addition, saccharification of raw cassava pulp needs the synergistic interaction of various starch-degrading and fiber-degrading enzymes to expose the complex structure of pulp to facilitate enzyme accessibility [5,74,75]. In summary, HL11Amy exhibited effective raw cassava pulp hydrolysis, which could be appropriate to promote further amylolytic enzymes in the non-thermal starch saccharification process by releasing solubilized starch.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization rather than discarding of cassava pulp will, therefore, reduce the negative impact on environmental and human health. On a dry weight basis, cassava pulp is mainly composed of starch (50-60%, w/w) with 15-27% (w/w) cellulose and hemicelluloses contents, pectin (7.0-7.3%, w/w), and lignin (3.4-4.6%, w/w) (Djuma'ali et al, 2012;Vaithanomsat et al, 2013). In general, the saccharification of cassava pulp to fermentable sugars used in the production of high value-added products requires the action of enzymes belonging to glycoside hydrolases (GHs), which hydrolyze the glycosidic bonds of starch, cellulose and hemicellulose contained in lignocellulose (Naumoff, 2011;Linares-Pastén, Andersson & Karlsson, 2014).…”
Section: Introductionmentioning
confidence: 99%